148k views
4 votes
Please help! i dont understand it
thank you

Please help! i dont understand it thank you-example-1
Please help! i dont understand it thank you-example-1
Please help! i dont understand it thank you-example-2
User Radium
by
6.3k points

1 Answer

2 votes

Answer:

1) True

2) True

3) False

4) True

5 True

Explanation:

1) y ≤ x - 3 and y ≥ -x - 2 ⇒ check if (3 , -2) is a solution of them

∵ -2 ≤ 3 - 3 ⇒ -2 ≤ 0 ⇒ true inequality

∵ -2 ≥ -3 - 2 ⇒ -2 ≥ -5 ⇒ true inequality

- Both of them are true

∴ (3 , -2) is a solution of y ≤ x - 3 and y ≥ -x - 2

True

2) y > -3x + 3 and y > x + 2 ⇒ check if (1 , 4) is a solution of them

∵ 4 > -3(1) + 3 ⇒ 4 > 0 ⇒ true inequality

∵ 4 > 1 + 2 ⇒ 4 > 3 ⇒ true inequality

- Both of them are true

∴ (1 , 4) is a solution of y > -3x + 3 and y > x + 2

True

3) y ≤ 3x - 6 and y > -4x + 2 ⇒ check if (0 , -2) is a solution of them

∵ -2 ≤ 3(0) - 6 ⇒ -2 ≤ 0 - 6 ⇒ -2 ≤ -6 ⇒ wrong inequality

∵ -2 > -4(0) + 2 ⇒ -2 > 0 + 2 ⇒ -2 > 2 ⇒ wrong inequality

- Both of them are wrong

∴ (0 , -2) is not a solution of y ≤ 3x - 6 and y > -4x + 2

False

4) 2x - y < 4 and x + y > -1 ⇒ check if (0 , 3) is a solution of them

∵ 2(0) - (3) < 4 ⇒ 0 - 3 < 4 ⇒ -3 < 4 ⇒ true inequality

∵ (0) + 3 > -1 ⇒ 3 > -1 ⇒ true inequality

- Both of them are true

∴ (0 , 3) is a solution of 2x - y < 4 and x + y > -1

True

5) y > 2x - 3 and y < -x + 6 ⇒ check if (-3 , 0) is a solution of them

∵ 0 > 2(-3) - 3 ⇒ 0 > -6 - 3 ⇒ 0 > -9 ⇒ true inequality

∵ 0 < -(-3) + 6 ⇒ 0 < 3 + 6 ⇒ 0 < 9 ⇒ true inequality

- Both of them are true

∴ (-3 , 0) is a solution of y > 2x - 3 and y < -x + 6

True

User Jubilee
by
5.3k points